The patient safety practices of emergency medical teams in disaster zones: a systematic analysis. Issue 6 (14th November 2019) - El-khani, Ussamah; Ashrafian, Hutan; Rasheed, Shahnawaz; Veen, Harald; Darwish, Ammar; Nott, David; Darzi, Ara
Abstract : Introduction: Disaster zone medical relief has been criticised for poor quality care, lack of standardisation and accountability. Traditional patient safety practices of emergency medical teams (EMTs) in disaster zones were not well understood. Improving the quality of healthcare in disaster zones has gained importance within global health policy. Ascertaining patient safety practices of EMTs in disaster zones may identify areas of practice that can be improved. Methods: A systematic search of OvidSP, Embase and Medline databases; key journals of interest; key grey literature texts; the databases of the WHO, Médecins Sans Frontieres and the International Committee of the Red Cross; and Google Scholar was performed. Descriptive studies, case reports, case series, prospective trials and opinion pieces were included with no limitation on date or language of publication. Results: There were 9685 records, evenly distributed between the peer-reviewed and grey literature. Of these, 30 studies and 9 grey literature texts met the inclusion criteria and underwent qualitative synthesis. From these articles, 302 patient safety statements were extracted. Thematic analysis categorised these statements into 84 themes (total frequency 632). The most frequent themes were limb injury (9%), medical records (5.4%), surgery decision-making (4.6%), medicines safety (4.4%) and protocol (4.4%). Conclusion: Patient safety practices of EMTs in disaster zones are weighted toward acute clinical care, particularly surgery. The management of non-communicable disease is under-represented. There is widespread recognition of the need to improve medical record-keeping. High-quality data and institutional level patient safety practices are lacking. There is no consensus on disaster zone-specific performance indicators. These deficiencies represent opportunities to improve patient safety in disaster zones.